Nested N-Grams and Circles

Geometry Level 3

Let n 5 n \geq 5 be a fixed odd positive integer and extend the above pentagrams to n n -grams.

For each positive integer m m , let P m P_{m} be the n n -gram inscribed in the circle C m C_{m} and C m + 1 C_{m + 1} be the circle inscribed in the n n -gram P m P_{m} .

Let r m r_{m} be the radius of each circle C m C_{m} .

If R ( n ) = m = 1 r m \displaystyle R(n) = \sum_{m = 1}^{\infty} r_{m} and R = lim n R ( n ) \displaystyle R = \lim_{n \to \infty} R(n) , find R r 1 \dfrac{R}{r_{1}} .


The answer is 1.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
Mar 8, 2020

Let n 5 n \geq 5 be a fixed positive odd integer.

m A O P = π n m\angle{AOP} = \dfrac{\pi}{n} and by Inscribed Angle Theorem m E P F = 1 2 m E O F m\angle{EPF} = \dfrac{1}{2}m\angle{EOF} \implies

m A P O = π 2 n m\angle{APO} = \dfrac{\pi}{2n}

A C O C = tan ( π n ) O C = A C tan ( π n ) \dfrac{AC}{OC} = \tan(\dfrac{\pi}{n}) \implies OC = \dfrac{AC}{\tan(\dfrac{\pi}{n})} and

P C = A C tan ( π 2 n ) = r 1 O C = r 1 A C tan ( π n ) PC = \dfrac{AC}{\tan(\dfrac{\pi}{2n})} = r_{1} - OC = r_{1} - \dfrac{AC}{\tan(\dfrac{\pi}{n})} \implies

r 1 = A C tan ( π n ) + A C tan ( π 2 n ) r_{1} = \dfrac{AC}{\tan(\dfrac{\pi}{n})} + \dfrac{AC}{\tan(\dfrac{\pi}{2n})} \implies A C ( tan ( π n ) + tan ( π 2 n ) tan ( π 2 n ) tan ( π n ) ) = r 1 AC(\dfrac{\tan(\dfrac{\pi}{n}) + \tan(\dfrac{\pi}{2n})}{\tan(\dfrac{\pi}{2n})\tan(\dfrac{\pi}{n})}) = r_{1}

h = A C = tan ( π 2 n ) tan ( π n ) tan ( π n ) + tan ( π 2 n ) r 1 \implies h = AC = \dfrac{\tan(\dfrac{\pi}{2n})\tan(\dfrac{\pi}{n})}{\tan(\dfrac{\pi}{n}) + \tan(\dfrac{\pi}{2n})}r_{1}

tan ( π n ) = tan ( 2 π 2 n ) = 2 tan ( π 2 n ) 1 tan 2 ( π 2 n ) \tan(\dfrac{\pi}{n}) = \tan(\dfrac{2\pi}{2n}) = \dfrac{2\tan(\dfrac{\pi}{2n})}{1 - \tan^2(\dfrac{\pi}{2n})} \implies

h = 2 tan ( π 2 n ) 3 tan 2 ( π 2 n ) r 1 h = \dfrac{2\tan(\dfrac{\pi}{2n})}{3 - \tan^2(\dfrac{\pi}{2n})}r_{1}

Let β ( n ) = tan ( π 2 n ) 3 tan 2 ( π 2 n ) h 1 = 2 β ( n ) r 1 = r 2 sin ( π n ) \beta(n) = \dfrac{\tan(\dfrac{\pi}{2n})}{3 - \tan^2(\dfrac{\pi}{2n})} \implies h_{1} = 2\beta(n) r_{1} = r_{2}\sin(\dfrac{\pi}{n}) r 2 = 2 β ( n ) sin ( π n ) r 1 \implies \boxed{r_{2} = \dfrac{2\beta(n)}{\sin(\dfrac{\pi}{n})}r_{1}}

In General r m = ( 2 β ( n ) sin ( π n ) ) m 1 r 1 \boxed{r_{m} = (\dfrac{2\beta(n)}{\sin(\dfrac{\pi}{n})})^{m - 1}r_{1}} and R ( n ) = m = 1 r m = sin ( π n ) sin ( π n ) 2 β ( n ) r 1 R(n) = \displaystyle\sum_{m = 1}^{\infty} r_{m} = \dfrac{\sin(\dfrac{\pi}{n})}{\sin(\dfrac{\pi}{n}) - 2\beta(n)}r_{1} .

For j ( n ) = 2 β ( n ) j ( n ) = π n 2 sec 2 ( π 2 n ) ( 3 + tan 2 ( π 2 n ) ( 3 tan 2 ( π 2 n ) ) 2 ) j(n) = 2\beta(n) \implies j'(n) = -\dfrac{\pi}{n^2}\sec^2(\dfrac{\pi}{2n})(\dfrac{3 + \tan^2(\dfrac{\pi}{2n})}{(3 - \tan^2(\dfrac{\pi}{2n}))^2})

R = lim n R ( n ) = lim n cos ( π n ) cos ( π n ) + sec 2 ( π 2 n ) ( 3 + tan 2 ( π 2 n ) ( 3 tan 2 ( π 2 n ) ) 2 ) r 1 \implies R = \lim_{n \rightarrow \infty} R(n) = \lim_{n \rightarrow \infty} \dfrac{-\cos(\dfrac{\pi}{n})}{-\cos(\dfrac{\pi}{n}) + \sec^2(\dfrac{\pi}{2n})(\dfrac{3 + \tan^2(\dfrac{\pi}{2n})}{(3 - \tan^2(\dfrac{\pi}{2n}))^2})}r_{1}

= 3 2 r 1 R r 1 = 3 2 = 1.5 = \dfrac{3}{2}r_{1} \implies \dfrac{R}{r_{1}} = \dfrac{3}{2} = \boxed{1.5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...